“Men are interested only in root crops”. Food security gendered policies in the Kingdom of Tonga - Gaia Cottino (Antropologia)
Recently the farlands of Oceania have entered a food security global discourse because of the climate change threat to food security. In the Kingdom of Tonga, such threat has promoted a large number of projects, often through female participation, imposing outsider values of food and reinforcing the nexus of gender and nature. This imposition on an indigenous system that embodies figuratively and literally the values of food, tackles the population’s food sovereignty, whose wellbeing is linked to land rights and access to food. By illustrating the core values of food throughout the Oceania cultural setting and the changing foodscape, land system and bodyscape, in which size and resources have a discursive interaction, I will discuss ethnographic data regarding a recent “urban horticulture” project aimed at building local food security, healthy eating and women empowerment. I will also question to which extent a “glocal” agenda, rather than a new rights framework for food and nature, can guarantee food sovereignty and the population wellbeing.